Congenital Microphthalmia with Intraorbital Cyst: A Rare Case Report - Bishow Raj Timalsina; Gulshan Bahadur Shrestha; Madhu Thapa (Case Reports in Ophthalmological Medicine)
Microphthalmia is considered to be the most common congenital malformation of the eye after congenital cataract. However, its association with intraorbital cyst is considered to be very rare. Most of the lesions are still misdiagnosed as orbital tumor and teratomas as there is a general paucity of data reported in literature. Herein, we report a rare case of congenital microphthalmia with intraorbital cyst in an eight-month-old male patient.